Identification of arboviruses in mosquito populations in KwaZulu-Natal, South Africa and the first record of Wyeomyia mitchellii in the Old World - Masoto, Nosipho Z.; Bester, Phillip A.; Snyman, Louwrens P.; Govender, Natasha; van Jaarsveldt, Danelle; Burt, Felicity J. (PLoS neglected tropical diseases, 2025)
Mosquito-borne viruses have the potential to spread and cause outbreaks with significant public and veterinary health consequences. Although historically a significant number of arboviruses were identified in South Africa with potential to cause sporadic outbreaks, there is limited information on the current situation in some regions of the country. Hence a study was initiated to investigate which arboviruses are currently circulating within mosquito populations in a major metropolitan area, eThekwini, KwaZulu-Natal Province. Mosquitoes were collected from seven sites throughout the metropole and a subset were screened for arboviruses from the families Togaviridae , Phenuiviridae and Peribunyaviridae. The subset of 1831 mosquitoes were collected between October 2020 and July 2021, identified morphologically, and pooled according to species, collection site and collection date. RNA was extracted from a total of 261 mosquito pools and screened using in-house nested and hemi-nested reverse transcriptase polymerase chain reaction (RT-PCR). Primers targeting conserved genes for each viral genus were used in a nested or hemi-nested two-step RT-PCR. Amplicons were sequenced to determine the virus species. Arboviral RNA was detected from 15/261 mosquito pools. The amplicons were subsequently sequenced using the Oxford Nanopore MinION. The positive samples included a Sindbis virus (SINV) isolate, three isolates of Witwatersrand virus (WITV), and 11 isolates of Bunyamwera virus (BUNV). Phylogenetic analysis of partial sequence data suggested that none were newly introduced but closely related isolates previously detected in the country. SINV is known to cause outbreaks of human disease after heavy rainfall, favoring an increase in mosquito populations. Bunyamwera virus has been associated with human febrile disease, but severe disease and regular outbreaks have not been reported previously and requires further investigation. The medical significance of WITV is currently unknown. Wyeomyia mitchellii , a New World species, is for the first time confirmed as an introduced species in South Africa and highlights the importance of vector surveillance. Identification of circulating viruses and raising the awareness of the presence of these viruses is important for early detection and determining the public health significance.